معوقات التداول السلمي للسلطة في العراق بعد عام 2005 (Journal of the College of Basic Education, 2025)
Many factors stand in the way of implementing the principle of peaceful transfer of power in the Iraqi constitutional system after 2005, some of which are related to legal matters, and some of which are related to political matters. All of these factors are of great importance to maintain the structure of constitutional systems that adopt the principle of peaceful transfer of power, as these factors negatively affect the course of the political process from various outlets, such as obstructing the electoral process and overlapping powers of authorities, in addition to the absence of political opposition and the spread of quotas in the political process, which negatively affects the achievement of the principle of peaceful transfer.